KAJIAN PELAYANAN RUTE MODA ANGKUTAN KOTA (ANGKOT) DI KOTA CIMAHI - , OKTA FAJAR SAPUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of Cimahi causing the high mobility, activity, and the number of population in Cimahi. Transportation is an important aspect to support the need of mobility and movement of the society. The high number of public transportation in Cimahi isnât supported by good services, so many people more interest to use private transportation. The impact is accumulation of vehicles on the road. This research was conducted to identify the movement patterns of Cimahi people, and then identify the service routes that currently exist today in the society's travel needs, to finally be able to give recommendations on structuring the route using public transportation order to service the routes to be more optimal. The method in this research is qualitative method, and then using descriptive statistical analysis techniques. Total 129 respondents was obtained using simple random sampling. Based on research conducted revealed that the public transportation routes are already capable of reaching most areas of Cimahi, that is equal to 68.71%. There are still plenty of routes public transportation is overlapping so that it becomes its own problems of congestion in Cimahi, in addition the application of existing routes have not been accessible because the public should switch several times to reach the location of transportation public routes to its destination.The user of public transportation is dominated by women (61.39%), then by the productive ages, and students (47.52%). This research also resulted in findings of potential road sections for the transportation. It is widely available in Cimahi Utara and Cimahi Selatan. Based on the findings and some of the problems of public transport in the Cimahi, so optimization of potential routes by modify the route using public transportation or feeder transportation could be one solution to the problem of public transport in the city of Cimahi.